Case Report: A Case of Valproic Acid-Induced Hyperammonemic Encephalopathy Associated With the Initiation of Lithium: A Re-duplicable Finding - Levy, Anna; Very, Etienne; Montastruc, François; Birmes, Philippe; Jullien, Adeline; Richaud, Louis (Frontiers in Psychiatry, 2022)
Introduction Hyperammonemic encephalopathy (HAE) is a serious adverse effect of valproate semisodium, which is facilitated by the potential for drug interaction. However, despite frequent co-prescription of valproate semisodium and lithium, the role of this combination in the occurrence of HAE has not been defined in the literature. This case report concerns the occurrence of HAE concomitant with the initiation of lithium in a 29-year-old patient who had been placed on valproate semisodium for a schizoaffective disorder. Case Report Due to a relapse while on a combined antipsychotic and mood-stabilizing therapy (paliperidone palmitate and valproate semisodium), a cross-taper from valproate semisodium to lithium was proposed. The initiation of lithium was accompanied by an acute confusional syndrome, an elevated serum valproate level and hyperammonemia suggestive of drug-induced HAE. The discontinuation of lithium and reduction of valproate semisodium led to neurological improvement, until a recrudescence of psychiatric symptoms justified a rechallenge of the combination within the framework of a new cross-taper. As soon as Lithium was re-initiated, an increase in the serum valproate level and hyperammonemia were again noted. Discussion The mechanisms of valproate-related HAE involve various metabolic pathways. In this case, exploration of the iatrogenic hypothesis focused on the imputability of concomitant cannabis use and co-prescriptions of benzodiazepines, antipsychotics, and in all likelihood, mood stabilizers. Conclusion Therefore, this case study suggests that Lithium plays a role in serum valproate level elevation, and supports the hypothesis of an association between an elevated serum valproate level, hyperammonemia and reversible encephalopathy. A more in-depth pharmacokinetic exploration would provide a better understanding of the mechanisms of these interactions and support for the benefit-risk balance associated with this frequent co-prescription.